Natural clinical tolerance to peanut in African patients is caused by poor allergenic activity of peanut IgE. Issue 6 (22nd March 2015) - Wollmann, E.; Hamsten, C.; Sibanda, E.; Ochome, M.; Focke‐Tejkl, M.; Asarnoj, A.; Önell, A.; Lilja, G.; Gallerano, D.; Lupinek, C.; Thalhamer, T.; Weiss, R.; et al.
Abstract: Background: In Africa, peanuts are frequently consumed, but severe allergic reactions are rare. We investigated immunological patterns of clinical tolerance to peanut in peanut‐sensitized but asymptomatic patients from central Africa compared to peanut‐allergic and peanut‐sensitized but asymptomatic patients from Sweden. Methods: Sera from allergic patients ( n  = 54) from Zimbabwe sensitized to peanut but without allergic symptoms to peanut, and sera from peanut‐allergic ( n  = 25) and peanut‐sensitized but asymptomatic ( n  = 25) patients from Sweden were analyzed toward peanut allergen components (Ara h 1–3, 6, 8–9) and other allergen molecules from important allergen sources using microarray. IgE to Ara h 2 peptide epitopes was analyzed, and allergenic activity was assessed by basophil activation assay. Results: Forty‐six percent of the African and all peanut‐allergic Swedish patients showed IgE toward one of the highly allergenic peanut allergens (Ara h 1–3, 6, 9). However, 48% of the African patients had IgE to cross‐reactive carbohydrate determinants (CCDs) with low allergenic activity and 60% of the Swedish asymptomatic patients had IgE against the PR protein Ara h 8. IgG and IgG4 specificities and levels could not discriminate between the African asymptomatic and Swedish peanut‐allergic patients. Asymptomatic patients almost lacked IgE to Ara h 2 peptides, which were recognized by peanut‐allergic patients. Peanut IgE from peanut asymptomatic patients showed poor allergenic activity compared with IgE from peanut‐allergic patients. Conclusions: Natural clinical tolerance to peanut in the African patients can be caused by IgE to low allergenic peanut components and by poor allergenic activity of peanut‐specific IgE.